2015
DOI: 10.1378/chest.14-2476
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation and ARDS in the ED

Abstract: BACKGROUND:Th ere are few data regarding mechanical ventilation and ARDS in the ED. Th is could be a vital arena for prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 62 publications
(63 reference statements)
3
47
1
Order By: Relevance
“…Seven days was chosen because the great majority of patients that develop ARDS after admission from the ED will do so within this time period. (14, 19, 21) Exclusion criteria were: 1) extubation within 24 hours; 2) death in the ED or within 24 hours; 3) chronic mechanical ventilation; 4) presence of tracheostomy; and 5) transfer to another hospital.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven days was chosen because the great majority of patients that develop ARDS after admission from the ED will do so within this time period. (14, 19, 21) Exclusion criteria were: 1) extubation within 24 hours; 2) death in the ED or within 24 hours; 3) chronic mechanical ventilation; 4) presence of tracheostomy; and 5) transfer to another hospital.…”
Section: Methodsmentioning
confidence: 99%
“…(14, 19) To improve these practices, the intervention aimed to address: 1) low tidal volume to prevent volutrauma; 2) appropriate PEEP setting to limit atelectrauma; 3) limitation of hyperoxia with rapid oxygen weaning; and 4) head-of-bed elevation for aspiration precautions. After intubation, the ED respiratory therapist obtained patient height with a tape measure, and tidal volume was indexed to PBW.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent multicenter observation study showed that a concerning number of patients receive suboptimal mechanical ventilation while in the ED. 8 The goals of the ED management of acute respiratory failure include minimizing work of breathing, appropriately using noninvasive positive-pressure ventilation (NIPPV), improving gas exchange, optimizing patient-ventilator synchrony, and limiting risk of ventilator-induced lung injury. Controversy remains about the role of noninvasive ventilation, timing of intubation, pharmacologic and nonpharmacologic rescue therapies and their role in the ED, and the role of extracorporeal membrane oxygenation (ECMO).…”
Section: Introductionmentioning
confidence: 99%